Skiing uphill : a sport ecology case study to save the snow - Solomon, Beth, active 2023; Stokowski, Sarah E. (London : Human Kinetics, Inc., 2022)
North College is a small, private university in the mountains of New England, and is primarily a National Collegiate Athletic Association Division III institution. There are four sports (men's alpine skiing, women's alpine skiing, men's Nordic skiing, and women's Nordic skiing), which compete at the National Collegiate Athletic Association Division I level. Both the Nordic and alpine ski teams must travel by college vehicle to their home training sites, which increases the cost of the team, and the carbon footprint of the teams. The alpine team travels 45 min to their local ski mountain, Wally Mountain, to train. Wally Mountain has been suffering from climate change. Higher temperatures and decreased snowfall have impacted the mountain and increased the cost of participating in alpine skiing. Wally Mountain must run many snowguns to create manmade snow to open.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Skis and skiing -- Environmental aspects -- New England -- Case studies; Sports -- Environmental aspects -- New England -- Case studies; Skis and skiing -- Costs -- Case studies